Analisis Peningkatan Debit Air Larian Akibat Pembangunan Perumahan Kota Sumber, Kabupaten Cirebon - Wardhani, Eka; Kurnia, Indianti; Irmansyah, Athaya Zahrani (Jurnal Serambi Engineering, 2025)
This study analyzes the increase in runoff caused by residential development in Sumber, Cirebon Regency, West Java. Housing development causes land conversion into impervious areas, which reduces rainwater infiltration and potentially increases the risk of downstream flooding. This study uses the calculation of runoff discharge before and after development, the rational method to measure runoff discharge. The predicted pre-development runoff was 0.205 m³/sec, which increased to 0.685 m³/sec after the development was completed; the potential increase in runoff was 0.481 m³/sec. The results show the significant impact of the development on the increase in runoff and potential flood risk. As a solution, environmentally sound drainage practices such as detention ponds and infiltration wells were developed to reduce the impact.